Complications after pelvic floor repair surgery (with and without mesh): short‐term incidence after 1873 inclusions in the French VIGI‐MESH registry. (23rd October 2019) - Fritel, X; Campagne‐Loiseau, S; Cosson, M; Ferry, P; Saussine, C; Lucot, J‐P; Salet‐Lizee, D; Barussaud, M‐L; Boisramé, T; Carlier‐Guérin, C; Charles, T; Debodinance, P; et al.
Abstract : Objective: To assess the short‐term incidence of serious complications of surgery for urinary incontinence or pelvic organ prolapse. Design: Prospective longitudinal cohort study using a surgical registry. Setting: Thirteen public hospitals in France. Population: A cohort of 1873 women undergoing surgery between February 2017 and August 2018. Methods: Preliminary analysis of serious complications after a mean follow‐up of 7 months (0–18 months), according to type of surgery. Surgeons reported procedures and complications, which were verified by the hospitals' information systems. Main outcome measures: Serious complication requiring discontinuation of the procedure or subsequent surgical intervention, life‐threatening complication requiring resuscitation, or death. Results: Fifty‐two women (2.8%, 95% CI 2.1–3.6%) experienced a serious complication either during surgery, requiring the discontinuation of the procedure, or during the first months of follow‐up, necessitating a subsequent reoperation. One woman also required resuscitation; no women died. Of 811 midurethral slings (MUSs), 11 were removed in part or totally (1.4%, 0.7–2.3%), as were two of 391 transvaginal meshes (0.5%, 0.1–1.6%), and four of 611 laparoscopically placed mesh implants (0.7%, 0.2–1.5%). The incidence of serious complications 6 months after the surgical procedure was estimated to be around 3.5% (2.0–5.0%) after MUS alone, 7.0% (2.8–11.3%) after MUS with prolapse surgery, 1.7% (0.0–3.8%) after vaginal native tissue repair, 2.8% (0.9–4.6%) after transvaginal mesh, and 1.0% (0.1–1.9%) after laparoscopy with mesh. Conclusions: Early serious complications are relatively rare. Monitoring must be continued and expanded to assess the long‐term risk associated with mesh use and to identify its risk factors. Tweetable abstract: Short‐term serious complications are rare after surgery for urinary incontinence or pelvic organ prolapse, even with mesh. Tweetable abstract: Short‐term serious complications are rare after surgery for urinary incontinence or pelvic organ prolapse, even with mesh.